Money Isn’t Everything, but It Helps If It Doesn’t Look Used: How the Physical Appearance of Money Influences Spending - Di Muro, Fabrizio; Noseworthy, Theodore J. (Journal of Consumer Research, 2013)
Abstract Despite evidence that currency denomination can influence spending, researchers have yet to examine whether the physical appearance of money can do the same. This is important because smaller denomination bills tend to suffer greater wear than larger denomination bills. Using real money in the context of real purchases, this article demonstrates that the physical appearance of money can override the influence of denomination. The reason being, people want to rid themselves of worn bills because they are disgusted by the contamination from others, whereas people put a premium on crisp currency because they take pride in owning bills that can be spent around others. This suggests that the physical appearance of money matters more than traditionally thought, and like most things in life, it too is inextricably linked to the social context. The results suggest that money may be less fungible than people think.